The Twelve Steps and Adolescent Recovery: A Concise Review. (January 2020) - Nash, Angela J
Recovery and long-term remission are the goals of treatment for substance use disorders, yet the majority of treated adolescents never stop using or resume using substances quickly after treatment. Thus, continuing care or recovery support services are common post-treatment recommendations for this group. Almost half of people who resolved significant substance use problems did so through participation in 12-step programs like Alcoholics Anonymous or Narcotics Anonymous. These recovery support programs are available online and in communities around the world. Yet <2% of these programs' members are under 21 years old. To help clinicians understand the 12-step explanatory model and facilitate clinical decision making on whether or when to refer individuals to these groups, this article summarizes the 12-step philosophy and practices and provides a concise review of research on adolescents' involvement in 12-step groups, including qualitative work that illuminates adolescents' reasons for resisting or engaging in 12-step practices.